Differenze teologiche tra la Vetus Syra e il Diatessaron - Lenzi, G. (Liber Annuus, 2006)
Abstract It is usually held that the Old Syriac Gospels depend upon the Diatessaron. In the present study the theological tendencies of the two versions are examined. Tatian stressed the virginity of Mary, introduced some Encratite variants, offered a Christology similar to Gnostic conceptions and was anti-Judaic. The translators of the Old Syriac Gospels stressed the relationship between Joseph and Jesus, introduced an important anti-Encratite variant, did not present any similarity with Gnostic ideas and were Jewish Christians. The conclusion is that the two versions were produced in two different communities and are independent of each other.